Low Serum Level of Vitamin D is Associated with Uterine Leiomyoma in the Chinese Population - Xinping Chen; Fen Yang; Zhiqiang Shen; Xuxiu Tang; Jiali Yu; Fujun Liu (Clinical and Experimental Obstetrics & Gynecology)
Background: The goal of this work was to compare the serum vitamin D level in women with uterine leiomyoma to that of controls, and to examine its association with the etiopathogenesis of this disease. Methods: This case-control study included 110 premenopausal women referred to a university hospital from January 2020 to December 2020. The study group consisted of 55 cases who underwent surgery for uterine fibroids, while the control group was comprised of 55 subjects without uterine fibroids. The number and volume of existing fibroids in each subject was assessed by transvaginal ultrasonography. Serum vitamin D status was determined by radioimmunoassay for 25-hydroxyvitamin D. Results: Average serum 25-hydroxyvitamin D levels in patients with uterine fibroids (20.52 ± 6.17 ng/mL) were significantly lower than in controls (24.18 ± 6.88 ng/mL; p = 0.004). Deficiency in 25-hydroxyvitamin D (i.e., <20 ng/mL) was more frequent in women with uterine fibroids (28/55, 50.91%) compared to controls (13/55, 23.64%; p = 0.001). A trend for negative correlation was found between serum 25-hydroxyvitamin D levels and total uterine fibroid volume (r = –0.18) in the study group (p = 0.20). No significant associations were found between serum 25-hydroxyvitamin D level and the number of fibroids (p = 0.38) or their location (p = 0.89). Conclusions: The serum vitamin D concentration is lower in Chinese women with uterine leiomyomas compared to controls. Vitamin D deficiency could therefore be a risk factor for uterine leiomyoma in the Chinese population.